Peran Islamic Green Banking terhadap Sustainable Development Goals di Indonesia - Candra Ningluthfi, Arseha; Arif Nurohman, Yulfan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Several countries are faced with a trade-off between economic growth and environmental degradation, including Indonesia. This problem then encourages stakeholders to create financial instruments that focus on project funding that is in accordance with the principles of Environment, Social, and Governance (ESG) and Sustainable Development Goals (SDGs). This is in line with sharia banking principles which can be a driving force for economic, social and environmental sustainability. This research aims to discuss the concept of Islamic Green Banking as a new sharia banking paradigm that integrates the roles of Islamic Banking and Green Banking in operational activities and their contribution to achieving Sustainable Development Goals in Indonesia. This research uses a literature review approach by compiling journal articles using Publish or Perish software and analyzing data using content analysis techniques. The result of this research is the concept of Islamic Green Banking which is divided into 5 perspectives, namely (a) Islamic Green Banking from the perspective of Sustainable Development Goals (SDGs) (b) Islamic Green Banking from a Technology perspective (c) Islamic Green Banking from a Green Finance perspective: ( d) Islamic Green Banking from a Company Operational perspective (e) Islamic Green Banking from a Maqasid Syariah perspective. Able to have an impact and contribution to Sustainable Development Goals (SDGs) in Indonesia. This has an impact on various Sustainable Development Goals (SDGs).